Q: 5x plus 3 equals -17

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

Yes.

-6x+3 = -7-5x 7+3 = 6x-5x 10=x

8x + 5x + 2x + 4x = 114 19x = 114 x = 6 then 5x + 3 = 5*6 + 3 = 33

79

x=-3

Related questions

Multiply the bottom equation by -1

If: x = 7 Then: y = (2*7)+3 = 17 And: 5x+y = (5*7)+17 = 52

When 5x+3 = 17 then x = 2.8 Therefore when 8x-y = 3 then x = 2.8 and y = 19.4

5x plus 3 does equal 3 plus 5x; commutative law.

33

9x + 5 = 5x + 179x + 5 - 5x = 179x - 5x = 4x5-4x=1717-5=1212 divided by 4 = 3x=3

5x + 3 = -12 5x =-12-3 =-15 x = -3

5x - 4x = 13 - 3 ie x = 10

5x+3 = 3x+11 5x-3x = 11-3 2x = 8 x = 4

-4x + 3 = -5x + 3add 5x to each sidex + 3 = 3subtract three from each sidex = 0

3 + 5x = 38 -> 5x = 35 -> x = 7

0. 6x + 3 = 5x + 141. 6x = 5x + 11 [subtracting 3]2. x = 11 [subtracting 5x]